TEACHERS’ OBSTACLES AND SOLUTIONS ON INTEGRATING ICT IN ENGLISH LANGUAGE TEACHING - Anisa Hersa Putri; Syafryadin Syafryadin (JALL (Journal of Applied Linguistics and Literacy), 2022)
Nowdays, in 21st century, it has been recognized for its easy access to technology for communication and gathering information. People are starting to use ICT to simplify or improve their work, as well as in education. This study aimed to find out (1) obstacles that English language teachers face while integrating ICT in teaching and learning process; and (2) solution of how to overcome those obstacles. This study used a survey research design. Questionnaire will be given to 35 samples of Junior High English teachers in public schools in Kota Bengkulu. Results showed that most teachers feel ready to undertake ICT tools in English teaching and learning process. In addition, there are several major obstacles in ICT implementation, such as lack of financial support, technological difficulties, academic dishonesty, and time limitations. It also uncovered that financial problem is the first obstacle to be solved in order to overcome others obstacles.